Where is the limit for overtime? Impacts of overtime on employees’ mental health and potential solutions: A qualitative study in China - Yu, Jiaoyang; Leka, Stavroula (Frontiers in Psychology, 2022)
Although Labor Law of the People's Republic of China stipulates the overtime system, overtime is still widespread in the IT industry. Through qualitative interviews, we explored the impact of overtime on employees’ mental health and life. The current study identified four main themes, namely overtime reasons, outcomes of overtime, influential factors and solutions to overtime challenges. Besides work-related reasons and cultural influence, it was found that employees may work overtime due to personal reasons, such as capability and personal qualities; the most frequent impacts reported were fatigue, depression, stress and interference with life; three predominant influential factors were timing of overtime, control and rewards; and overtime conditions could be improved in practical and emotional ways. The study’s findings highlight the importance of the design of flexible working time arrangements for avoiding fatigue and improving employees’ work-life balance, enhancement of schedule arrangement for avoiding daily work interruption and last-minute tasks, and optimization of rewarding systems for avoiding complaints and facilitating voluntary overtime. Results suggest that mental health and work-life balance can be promoted by organizational initiatives focusing on minimizing excessive job demands, increasing psychosocial resources, supporting boundary management, and enhancing perceived flexibility.